Computerized Image Analysis in Differentiation of Skin Lesions Caused by Electrocution, Flame Burns, and Abrasion - İNANICI, MEHMET AKİF (WILEY, 2009)
In the practice of forensic science, sometimes, it is not easy to understand whether skin lesion is due to electrocution and to differentiate the thermal burns and abrasion-type lesions, especially when electricity source cannot be revealed by death science investigation. Based on the causes of the lesions, cases were classified into three groups. Group 1 included 30 deaths from electrocution. Group 2 included 30 deaths with flame burns. Group 3 included 30 deaths from traffic accident cases, which had abrasions. In this study, epidermal nuclear area, perimeter, nuclear form factor, nuclear minimum axes, nuclear maximum axes, and minimum axes/maximum axes ratio were measured. As a result, we think that computerized image analysis beside light microscopic examination can be useful in the differentiation of the electrocution, flame burn, and abrasion type lesions.
Keywords: forensic medicine; computerized image analysis; electrocution; flame burns; abrasion; autopsy; ELECTRICAL INJURY; MECHANISM